DOI: 10.4995/thesis/10251/162071
|View full text |Cite
|
Sign up to set email alerts
|

De la tabla al lienzo. Evolución técnica del soporte pictórico en la Escuela Valenciana del Renacimiento pleno al naturalismo barroco

Abstract: The combined use of cross-section analysis and other stratigraphic recording systems in the cleaning of two panel paintings from the fifteenthand sixteenth-century.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…1550-ca. 1670) [15,16]. In an earlier work [16], the authors demonstrated some collaborations and mutual influences among the painters Vicente Castelló, Francisco Ribalta and his son Juan Ribalta, and Jerónimo Rodríguez de Espinosa and his son Jerónimo Jacinto de Espinosa (see Fig.…”
Section: -Research Aimmentioning
confidence: 92%
“…1550-ca. 1670) [15,16]. In an earlier work [16], the authors demonstrated some collaborations and mutual influences among the painters Vicente Castelló, Francisco Ribalta and his son Juan Ribalta, and Jerónimo Rodríguez de Espinosa and his son Jerónimo Jacinto de Espinosa (see Fig.…”
Section: -Research Aimmentioning
confidence: 92%